Association of patient satisfaction with direct oral anticoagulants and the clinical outcomes: Findings from the SAKURA AF registry. Issue 1 (July 2020) - Hori, Koichiro; Okumura, Yasuo; Koichi, Nagashima; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Kuronuma, Keiichiro; Oiwa, Koji; Matsumoto, Michiaki; Kojima, Toshiaki; Arima, Ken; Kotani, Tomobumi; et al.
Highlights: The patient satisfaction of direct oral anticoagulant users in atrial fibrillation was assessed by the Anti-Clot Treatment Scale (ACTS) score. Upon univariate analysis, lower ACTS benefit scores were significantly associated with an increased risk of a stoke/systemic embolism (SE). A low benefit score remained an independent predictor of a stroke/SE even after a multivariate adjustment. The ACTS burden scores were not associated with any clinical events. Abstract: Background: The burden or benefit of anticoagulation treatment affects patient satisfaction, which may in turn affect the adherence to the treatment and subsequent outcomes. Thus, we hypothesized that the patient satisfaction with direct oral anticoagulants (DOACs) may influence the clinical outcome in patients with atrial fibrillation (AF). Methods and Results: We investigated the clinical outcomes among 719 DOAC users (age 71.9 ± 9.1 years, 184 females, and 449 persistent AF) enrolled in the SAKURA AF Registry who completed a satisfaction questionnaire with anticoagulation therapy by means of the Anti-Clot Treatment Scale (ACTS), which included 12-item burden and 3-item benefit scales. During a 41.8-month-follow-up, a stroke/systemic embolism (SE) occurred in 27 patients (3.8%) and major bleeding events in 25 (3.5%). A univariate Cox regression analysis revealed that an older age, persistent AF, higher CHA2 DS2 -VASc score, no history of AF ablation, lower creatinine clearance, and lower ACTS benefit scores were significantly associated with an increased risk of a stroke/SE, but not with major bleeding events. A low benefit score remained an independent predictor of a stroke/SE even after a multivariate adjustment. The ACTS burden scores were not associated with any clinical events. Conclusions: We found a strong association between a low benefit satisfaction and increased stroke risk. We should follow patients carefully to educate them on treatment importance for patients unsatisfied with the benefits of DOACs for stroke prevention.